Emtricitabine, propofol and tenofovir compound tablet and preparation method thereof
By optimizing the preparation process of emtricitabine propofol tenofovir compound tablets, including the combination of particle size and filler, the problem of poor stability of propofol tenofovir in the prior art is solved, and better flow is achieved and stability, and show better stability under light and accelerated conditions.
Patent Information
- Application Number
- CN202411241301.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-05
AI Technical Summary
The stability of propofol tenofovir in the existing emtricitabine propofol tenofovir compound tablets is poor, especially in the presence of emtricitabine, and the existing packaging methods are complicated to operate.
By preparing a first emtricitabine propofol tenofovir compound tablet, the first part consisting of tenofovir hemifumarate alaphenolamine, emtricitabine, filler and disintegrant, The particle size is optimized to 100-300μm, and it is pressed by dry granulation and a three-dimensional mixer, followed by film coating, using a combination of sodium chloride and microcrystalline cellulose and hydrogenated vegetable oil as lubricant to improve stability.
Improve the stability and fluidity of propofol tenofovir, ensure that the first particle prepared has good fluidity and stability, and the main drug content in the tablet reaches the commercially available through the optimization of particle size and filler. The mixing uniformity of the formulation significantly improves the stability under light and accelerated conditions.
Smart Images

Figure BDA0005029357550000041 
Figure BDA0005029357550000051 
Figure BDA0005029357550000071
Abstract
Description
Technical Field
[0001] The present invention relates to the field of medical technology, and in particular to an emtricitabine and tenofovir alafenamide compound tablet and a preparation method thereof. Background Art
[0002] Acquired immunodeficiency syndrome (AIDS) is a malignant infectious disease caused by the human immunodeficiency virus (HIV); HIV is an RNA virus that, after infecting host cells, attacks the human immune system and disrupts the immune balance by multiplying in large numbers and destroying CD4+T lymphocytes, thereby reducing the body's resistance and infecting other diseases, leading to various complex infections and death.
[0003] In order to solve the problem of HIV drug resistance, oral combination drugs are used to target multiple HIV proteins or different binding sites on the same protein, which can achieve long-term permanent suppression of HIV and extend the life expectancy of HIV patients. Currently, a variety of combination preparations have been approved for marketing.
[0004] Tenofovir alafenamide fumarate was developed by Gilead Sciences, Inc., USA. Its name is tenofovir alafenamide fumarate, with the patent number GS-7340 and the English abbreviation TAF. It is the second oral prodrug of tenofovir. It is formed by changing the prodrug groups on the two hydroxyl groups in the phosphoric acid based on the structure of tenofovir disoproxil fumarate (TDF), that is, changing disoproxil to an amide and a phenol ester. Since TAF is almost not decomposed in the blood and is directly transported to lymphocytes and macrophages in large quantities and decomposed into tenofovir, and then phosphorylated to form active ingredients, the dosage is small and the side effects are low under the same conditions.
[0005] The drug used in combination with tenofovir alafenamide and emtricitabine is called emtricitabine alafenamide tenofovir tablets (II), which was first approved by the US FDA in 2016 and is called Descovy in English. It was approved for marketing in China in 2018 for the treatment of HIV-1 infection in adults and adolescents. To this end, the Chinese patent CN107847450A applied by Gilead discloses a pharmaceutical preparation containing tenofovir and emtricitabine, which consists of 200 mg of emtricitabine, 28 mg of tenofovir alafenamide hemifumarate, 28 mg of cross-linked sodium carboxymethyl cellulose, 88 mg of microcrystalline cellulose, and 7 mg of magnesium stearate. Emtricitabine, tenofovir alafenamide hemifumarate, microcrystalline cellulose and cross-linked sodium carboxymethyl cellulose are dry granulated, and then mixed with magnesium stearate, tableted and coated, with a tablet weight of 350 mg / tablet. The storage stability of tenofovir alafenamide in the above-mentioned tablets is poor, especially in the presence of emtricitabine; while the stability can be improved by placing a desiccant in the packaging bottle, the operation is obviously very cumbersome.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The problem solved by the invention is that the stability of tenofovir alafenamide in the existing compound tablets still needs to be improved.
[0008] In order to solve the above problems, the present invention provides an emtricitabine and tenofovir alafenamide compound tablet, comprising a tablet core, wherein the tablet core comprises 300-330 parts of first particles, 20-40 parts of emtricitabine, and 3-5 parts of lubricant, wherein the first particles are composed of 28 parts of tenofovir alafenamide hemifumarate, 160-180 parts of emtricitabine, 85-90 parts of filler, 25-30 parts of disintegrant, and 3-5 parts of lubricant, and the particle size D 90 100-300μm.
[0009] Preferably, the particle size D of the first particles is 90 The particle size D of emtricitabine is 150-250 μm. 90 Preferably, the particle size D of the first particles is 150-200 μm. 90 is 200μm.
[0010] Preferably, the emtricitabine and tenofovir alafenamide combination tablets include 307-327 parts of first particles, 20-40 parts of emtricitabine, and 3-5 parts of lubricant, wherein the first particles are composed of 28 parts of tenofovir alafenamide hemifumarate, 160-180 parts of emtricitabine, 88 parts of filler, and 28 parts of disintegrant.
[0011] Preferably, the lubricant is any one of magnesium stearate, stearic acid, hydrogenated vegetable oil, glyceryl behenate, and sodium stearyl fumarate.
[0012] Preferably, the disintegrant is any one of starch, cellulose, cross-linked PVP, sodium starch glycolate, and sodium carboxymethyl cellulose.
[0013] Preferably, the filler is at least one of microcrystalline cellulose, mannitol, lactose monohydrate, and sodium chloride. Preferably, the filler is composed of microcrystalline cellulose: sodium chloride = 1:0.5-1:3, wherein the model of microcrystalline cellulose is: AvicelPH113.
[0014] The present invention also provides a method for preparing emtricitabine and tenofovir alafenamide compound tablets, comprising the following steps:
[0015] S1. Grind tenofovir alafenamide hemifumarate and emtricitabine and control the particle size D 90 150-200 μm, for later use;
[0016] S2, mixing the prescribed amount of tenofovir alafenamide hemifumarate, emtricitabine, a filler, a disintegrant, and a lubricant, and performing dry granulation with a dry granulator to obtain first granules;
[0017] S3. The first granules, the remaining amount of emtricitabine and the lubricant are mixed by a three-dimensional mixer for 5-10 minutes, and the materials are pressed into 350 mg tablet cores, a total of 1000 tablets, and then film-coated.
[0018] Preferably, the particle size D of emtricitabine after crushing in step S1 is 90 is 150μm.
[0019] Preferably, the process parameters of the dry granulation are: feeding speed 10-20 Hz, roller pressure 0.6-0.9 MPa, roller speed 12-18 Hz. Specifically, the feeding speed may be 16 Hz, roller pressure 0.8 MPa, roller speed 12 Hz; or the feeding speed may be 12 Hz, roller pressure 0.9 MPa, roller speed 15 Hz, or the feeding speed may be 18 Hz, roller pressure 0.7 MPa, roller speed 18 Hz.
[0020] Compared with the prior art, the emtricitabine-tenofovir alafenamide compound tablets and the preparation method of the present invention have the following beneficial effects: 1) by directly compressing part of the emtricitabine into tablets and granulating, the local content of tenofovir alafenamide in the first granules is increased while the probability of contact with emtricitabine is reduced, thereby improving its stability and ensuring that the prepared first granules have good fluidity; 2) the applicant found that different types of microcrystalline cellulose can affect the stability of the mixed material; at the same time, it was unexpectedly found that: sodium chloride and microcrystalline cellulose produce a synergistic effect when mixed in a ratio of 1:3, and the stability of the material can be further improved; in addition, hydrogenated vegetable oil is used to replace weakly alkaline magnesium stearate, which can improve the stability under light conditions; 3) by optimizing the particle size of the first granules and emtricitabine, the main drug content in the tablet can reach the mixing uniformity with commercially available preparations. DETAILED DESCRIPTION
[0021] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. The tenofovir alafenamide described in the present invention is usually in the form of a pharmaceutically acceptable salt, such as a monofumarate or a hemifumarate, preferably tenofovir alafenamide hemifumarate; similarly, emtricitabine can exist in a solvated or unsolvated form, preferably in the form of emtricitabine free base.
[0022] It should be noted that, unless otherwise specified, the dosages described in this application refer to the amount of the active ingredient tenofovir alafenamide or emtricitabine. For example, 25 mg of tenofovir alafenamide or 28 mg of tenofovir alafenamide hemifumarate have the same active ingredient, and the mannitol described in this application is produced by Roquette, France, with the trade name PEARLITOL, model 50C.
[0023] Experimental Example 1 Effect of the Addition Ratio of FTC in the First Particle on the Stability and Angle of Repose of the Mixed Material
[0024] Increasing the drug load of tenofovir alafenamide will improve its stability. Combined with the bioequivalence test, the dosage of tenofovir alafenamide in the tablet is determined to be 25 mg. Although emtricitabine will affect the stability of tenofovir alafenamide, especially under high temperature and humidity conditions, the process of dry granulating emtricitabine and tenofovir alafenamide and then mixing them for tableting is simple and can meet the production requirements of tablets.
[0025] Since the compressibility and fluidity of emtricitabine are not ideal and the total content is as high as 64%, the effect of preparing tablet cores by direct tableting is extremely poor, and tenofovir alafenamide is sensitive to water, and it is currently unrealistic to prepare tablets by wet granulation. Therefore, the applicant prepared the first granules with large particle size and conducted the following experiments on the amount of emtricitabine in the first granules:
[0026] 280 g of tenofovir alafenamide hemifumarate, 280 g of cross-linked carboxymethyl cellulose sodium, 880 g of microcrystalline cellulose, 25 g of magnesium stearate and a certain amount of emtricitabine were dry granulated. The specific process parameters were feed rate of 9 Hz, roller pressure of 0.8 MPa, roller speed of 16 Hz, granulation speed of 15 Hz to obtain the first granules, D 90 The first particles, the remaining emtricitabine and magnesium stearate were mixed, and the angle of repose of the material was detected. At the same time, part of the material was stored at 40°C / 75%RH for one month to detect the total amount of degradation products of tenofovir alafenamide hemifumarate in the material. The results are shown in Table 1.
[0027] Table 1 The amount of emtricitabine in the first granule and its effect on material stability and compressibility
[0028]
[0029]
[0030] Take 50g of the prepared mixed material and slowly add it from the upper funnel, so that the auxiliary materials are gradually accumulated on the bottom plate through the buffer of the funnel to form a cone until the highest cone is obtained. Determine the height H of the cone and calculate the angle of repose as follows: α=arctg(H / R) where α is the angle of repose and R is the radius of the bottom plate. When the angle of repose is ≤30°, the fluidity of the material to be prepared is very good, when the angle of repose is 36-40°, the fluidity of the material to be prepared is better, and when the angle of repose is 42-45°, the material to be prepared may have fluidity; when it is higher than the above-mentioned method for detecting degradation products or total impurities corresponding to tenofovir alafenamide is prior art and will not be described in detail here.
[0031] From the above table, we can see that the first particle (particle size D 90 200 μm) can be regarded as the smallest material unit. Reducing the amount of emtricitabine can increase the relative content of tenofovir alafenamide in the first granules, which is beneficial to improving its storage stability. However, emtricitabine without dry granulation will change the compressibility of the material. When the amount of emtricitabine in the first granules accounts for 60-80% of the total amount, the stability of the mixed material for preparing the tablet core is good and can meet the tableting requirements. In fact, when the amount of emtricitabine in the first granules is less than 50% of the total amount, not only the parameter angle of repose is lost, but the mixed material cannot be used for tableting at all.
[0032] In the early stage of the experiment, the applicant tried to dry granulate only tenofovir alafenamide, and then mixed it with emtricitabine and a lubricant for tablet compression and coating. The poor compressibility of the mixed material resulted in a large difference in tablet weight, which was difficult to meet production needs. After tenofovir alafenamide was dry granulated with microcrystalline cellulose, it was dry granulated again with emtricitabine. Due to the change in material properties, the uniformity of the secondary dry granulation did not meet the standards, the process was relatively complicated, and the stability was obviously poor.
[0033] Experimental Example 2 Effect of fillers on material stability
[0034] The applicant was able to improve stability by increasing the particle size of the first granules while reducing the proportion of emtricitabine in the first granules, but this still needs to be improved compared with other drugs; it is generally believed that moisture is an important factor affecting the stability of tenofovir alafenamide, while fillers are generally believed to have no effect on stability.
[0035] Due to the different types of excipients, there are slight differences in their performance. The particle size and bulk density of different types of microcrystalline cellulose vary with the type, and their physical and chemical properties also vary. Therefore, the applicant unexpectedly found that the stability of tablets prepared by type Avicel PH113 is significantly better than that of conventional Avicel PH101 and Avicel PH102. The applicant used fillers of different types and types to prepare the first granules, which contained 80% of emtricitabine. The first granules were then mixed with the remaining amount of emtricitabine and lubricant, and the mixed materials were stored at 40°C / 75%RH for 1 month for stability test. The results are shown in Table 2.
[0036] Table 2 Effect of different fillers on material stability
[0037] Fillers TAF total impurity content % AvicelPH102 0.63% AvicelPH113 0.52% AvicelPH301 0.67% Colloidal Silica 0.76% Mannitol 0.78% Sodium chloride 0.59% Lactose monohydrate: Avicel PH113 = 1:1 0.81% Sodium chloride: Avicel PH113 = 1:1 0.47% Colloidal silica: Avicel PH113 = 1:1 0.79% Mannitol: Avicel PH113 = 1:1 0.82% Sodium chloride: Avicel PH113 = 1:2 0.42% Sodium chloride: Avicel PH113 = 1:3 0.38% Sodium chloride: Avicel PH113 = 1:4 0.47% Sodium chloride: Avicel PH113 = 1:5 0.54%
[0038] As can be seen from the above table, common fillers do not affect the stability of tenofovir alafenamide, and compared with the common Avicel PH102, the microcrystalline cellulose model Avicel PH113 can further improve the stability of tenofovir alafenamide. The inventor unexpectedly found that when sodium chloride: Avicel PH113 = 1:3, the degradation rate of tenofovir alafenamide can be reduced to 0.38%, and the stability of tenofovir alafenamide can be significantly improved in the long-term accelerated test. The possible reasons are: sodium chloride is a neutral compound with very stable physical and chemical properties, and it will not react chemically with emtricitabine and tenofovir alafenamide, and the compatibility is very good. Sodium chloride is easily soluble in water, which is conducive to the dissolution and release of the active ingredient after the process is improved; in addition, the water content of sodium chloride is very low and in the production environment with a relative humidity of less than 70%, its hygroscopicity is very low, and sodium chloride is a cubic crystal with very good compressibility, which is conducive to tableting at a lower pressure after the process is improved.
[0039] Experimental Example 3 Effect of Particle Size on Tablet Preparation
[0040] The applicant found that when the above-mentioned excipients were used to prepare tablets, the particle size of the first granules obtained by dry granulation increased, which affected the mixing uniformity of the final mixed material. Therefore, the applicant used sodium chloride: Avicel PH113 = 1:3 as a filler, 80% of emtricitabine and tenofovir alafenamide were dry granulated to prepare first granules of different particle sizes, the remaining emtricitabine was micronized, and the content uniformity at different particle sizes was measured, and the material was stored at 40°C / 75%RH for 1 month to determine the total impurity content of tenofovir alafenamide. The results are shown in Table 3.
[0041] The content uniformity was determined in accordance with the content uniformity test method (General Rule 0941) of Part IV of the 2020 edition of the "Chinese Pharmacopoeia". Ten samples were taken after mixing the materials for 10 minutes for each parameter condition, and the relative content Xi of tenofovir alafenamide was determined with the labeled amount as 100. The mean value and standard deviation S (of the relative content) and the absolute value A of the difference between the labeled amount and the mean were calculated, and A+2.2S was used as the content uniformity index of the test sample.
[0042] Table 3 Effect of different particle sizes on material mixing uniformity and stability
[0043]
[0044]
[0045] As can be seen from Table 3, the total impurity content of tenofovir alafenamide is proportional to the particle size of the first granule as a whole. This may be because the present application reduces the content of emtricitabine in the first granule, thereby increasing the amount of tenofovir alafenamide in the local microunit of the first granule, thereby improving the overall stability; As can be seen from Table 3, the content uniformity of the material is affected by the particle size of the first granule and the emtricitabine directly tableted. The inventor unexpectedly found that: when the particle size D of the first granule is 90 = 250 μm, particle size D of emtricitabine 90 =150μm, on the contrary, the mixing uniformity of the materials is better. At the same time, the solubility of tenofovir alafenamide and emtricitabine in the prepared tablets within 20min reaches more than 90%. The possible reason is that the relative content of the disintegrant and the filler in the first granules increases, resulting in changes in the material properties. By controlling the particle size of the first granules and the emtricitabine directly used for tableting, the fluidity of the material is significantly improved. The inventors conducted preliminary tests on further increasing the particle size of the first granules. At this time, the dissolution performance of the prepared tablets obviously cannot meet the requirements, and there is an obvious lack of bioequivalence with the original drug.
[0046] Example 1
[0047] An emtricitabine alafenamide and tenofovir alafenamide compound tablet, the prescription composition of 1000 tablets is as follows:
[0048]
[0049]
[0050] The following preparation process is adopted:
[0051] S1. Grind tenofovir alafenamide hemifumarate and emtricitabine and control the particle size D 90 150μm;
[0052] S2, the prescribed amount of tenofovir alafenamide hemifumarate, emtricitabine, microcrystalline cellulose (model Avicel PH113, sodium chloride, cross-linked sodium carboxymethyl cellulose, and magnesium stearate are mixed, and dry granulated by a dry granulator to obtain the first granule with a particle size D 90 The dry granulation process parameters are as follows: feeding speed 9HZ, roller pressure 0.8MPa, roller speed 16HZ;
[0053] S2, mixing the first granules and the remaining amount of emtricitabine and magnesium stearate using a three-dimensional mixer for 10 minutes;
[0054] S3. The material is compressed into 350 mg tablet cores, 1000 tablets in total, and then film-coated.
[0055] Example 2
[0056] An emtricitabine alafenamide and tenofovir alafenamide compound tablet, the prescription composition of 1000 tablets is as follows:
[0057]
[0058]
[0059] The following preparation process is adopted:
[0060] S1. Grind tenofovir alafenamide hemifumarate and emtricitabine and control the particle size D 90 150μm;
[0061] S2, the prescribed amount of tenofovir alafenamide hemifumarate, emtricitabine, microcrystalline cellulose (model Avicel PH113, sodium chloride, cross-linked sodium carboxymethyl cellulose, and magnesium stearate are mixed, and dry granulated by a dry granulator to obtain the first granule with a particle size D 90 The dry granulation process parameters are as follows: feeding speed 8HZ, roller pressure 0.9MPa, roller speed 12HZ;
[0062] S2, mixing the first granules and the remaining amount of emtricitabine and magnesium stearate using a three-dimensional mixer for 8 minutes;
[0063] S3. The material is compressed into 350 mg tablet cores, 1000 tablets in total, and then film-coated.
[0064] Example 3
[0065] An emtricitabine alafenamide and tenofovir alafenamide compound tablet, the prescription composition of 1000 tablets is as follows:
[0066]
[0067]
[0068] The following preparation process is adopted:
[0069] S1. Grind tenofovir alafenamide hemifumarate and emtricitabine and control the particle size D 90 150μm;
[0070] S2, the prescribed amount of tenofovir alafenamide hemifumarate, emtricitabine, microcrystalline cellulose (model Avicel PH113, sodium chloride, cross-linked sodium carboxymethyl cellulose, and magnesium stearate are mixed, and dry granulated by a dry granulator to obtain the first granule with a particle size D 90 The dry granulation process parameters are as follows: feeding speed 10HZ, roller pressure 0.7MPa, roller speed 14HZ;
[0071] S2, mixing the first granules and the remaining amount of emtricitabine and magnesium stearate using a three-dimensional mixer for 9 minutes;
[0072] S3. The material is compressed into 350 mg tablet cores, 1000 tablets in total, and then film-coated.
[0073] Example 4
[0074] An emtricitabine alafenamide and tenofovir alafenamide compound tablet, the prescription composition of 1000 tablets is as follows:
[0075]
[0076] The following preparation process is adopted:
[0077] S1. Grind tenofovir alafenamide hemifumarate and emtricitabine and control the particle size D 90 150μm;
[0078] S2, the prescription amount of tenofovir alafenamide hemifumarate, emtricitabine, microcrystalline cellulose (model Avicel PH113, sodium chloride, cross-linked sodium carboxymethyl cellulose, hydrogenated vegetable oil was mixed, and dry granulated by a dry granulator to obtain the first granule with a particle size D 90 The dry granulation process parameters are as follows: feeding speed 9HZ, roller pressure 0.8MPa, roller speed 14HZ;
[0079] S2, mixing the first granules, the remaining amount of emtricitabine and hydrogenated vegetable oil using a three-dimensional mixer for 9 minutes;
[0080] S3. The material is compressed into 350 mg tablet cores, 1000 tablets in total, and then film-coated.
[0081] Comparative Example 1
[0082] Commercially available tablets, trade name: Descovy.
[0083] Comparative Example 2
[0084] The same formulation as in Example 1 was used, and the specific preparation process was as follows: S1, tenofovir alafenamide hemifumarate and emtricitabine were crushed and the particle size D was controlled. 90 S2, the prescription amount of tenofovir alafenamide hemifumarate, microcrystalline cellulose (model Avicel PH113), mannitol, and cross-linked sodium carboxymethyl cellulose are dry granulated by a dry granulator, and the process parameters are: feeding speed 15rpm, roller pressure 38bar, roller gap 0.6mm, and the particle size D of the first granule obtained after granulation is 90 150μm;
[0085] S2, mixing the first granules, emtricitabine, cross-linked carboxymethyl cellulose sodium, and magnesium stearate using a three-dimensional mixer for 9 minutes;
[0086] S3. The material is compressed into 350 mg tablet cores, 1000 tablets in total, and then film-coated.
[0087] Comparative Example 3
[0088] The same formulation composition and preparation process as in Example 1 were used, with the only difference being that the process parameters for dry granulation were: feed speed 18 rpm, roller pressure 28 bar, and roller gap 0.9 mm.
[0089] Comparative Example 4
[0090] The components and the same process as those of publication number CN107847450A are used, but the difference is that microcrystalline cellulose (model Avicel PH113): sodium chloride = 3:1 is used to replace the commonly used microcrystalline cellulose Avicel PH102.
[0091] Three samples of the tablets prepared in Examples 1-4 and Comparative Examples 1-3 were taken and placed under illumination (5000 lx) for 10 days and under accelerated conditions (40°C-RH75%) for 1 and 3 months, and the total impurity content of tenofovir alafenamide hemifumarate was detected and the average value was calculated. The results are shown in Table 4.
[0092] Table 4 Stability data
[0093]
[0094] As can be seen from Table 4, Examples 1-4 in the present application creatively adjust the preparation process of emtricitabine tenofovir alafenamide compound tablets, and optimize the components on this basis. The prepared tablets do not require the addition of a desiccant, and have better stability than commercially available preparations under light conditions and accelerated test conditions, and emtricitabine exhibits good stability during the experiment; generally, hydrogenated vegetable oil and magnesium stearate are both hydrophobic lubricants, although they have better certain adhesive properties and weaker hydrophobicity, they can effectively reduce the force required to push the tablet out of the die hole to improve compressibility; and the present application unexpectedly found that: relative to weakly alkaline magnesium stearate, hydrogenated vegetable oil as a lubricant can improve the stability of tenofovir alafenamide hemifumarate in the tablets prepared in the present application under light conditions.
[0095] 10 samples of the tablets prepared in Examples 1-4 and Comparative Examples 1-3 were taken to detect the content percentages of tenofovir alafenamide hemifumarate and emtricitabine, and the content average and standard deviation were calculated, and the coefficient of variation CV representing the mixing uniformity was calculated from them = (standard deviation SD / average value M) × 100%, and the results are shown in Table 5. The detection methods of tenofovir alafenamide hemifumarate and emtricitabine are prior art and will not be described in detail here.
[0096] Table 5 Mixing uniformity data
[0097]
[0098] If the concentration of antiviral drugs fluctuates due to uneven mixing, it may cause drug resistance of the virus, especially for compound preparations, the mixing uniformity of tablets is crucial. As can be seen from the above table, the tablets prepared in Examples 1-4 of the present application are optimized by optimizing the components and particle size after changing the preparation process, so that they have a content uniformity basically consistent with that of Comparative Example 1, while Comparative Example 2 uses another preparation process to make the mixing uniformity of the main drug worse, and Comparative Example 3 shows that the process parameters of dry granulation will affect the content uniformity of the main drug in the tablets, and also make the mixing uniformity of the main drug worse; relative to Comparative Example 1, only changing the composition of the filler in Comparative Example 4 will also affect the mixing uniformity. The solubility of tenofovir alafenamide hemifumarate and emtricitabine in the tablets prepared in Examples 1-4 of the present application within 20 minutes is more than 90%, and the solubility is basically consistent with Comparative Example 1.
[0099] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. An emtricitabine and tenofovir alafenamide compound tablet, characterized in that: The tablet core comprises 300-330 parts of first particles, 20-40 parts of emtricitabine, and 3-5 parts of lubricant, wherein the first particles are composed of 28 parts of tenofovir alafenamide hemifumarate, 160-180 parts of emtricitabine, 85-90 parts of filler, 25-30 parts of disintegrant, and 3-5 parts of lubricant, and the particle size D 90 100-300μm.
2. The emtricitabine alafenamide and tenofovir alafenamide compound tablets according to claim 1, characterized in that: The particle size D of the first particle 90 The particle size D of emtricitabine is 150-250 μm. 90 150-200μm.
3. The emtricitabine alafenamide and tenofovir alafenamide compound tablets according to claim 1, characterized in that: The emtricitabine and tenofovir alafenamide combination tablets include 307-327 parts of first particles, 20-40 parts of emtricitabine, and 3-5 parts of lubricants, wherein the first particles are composed of 28 parts of tenofovir alafenamide hemifumarate, 160-180 parts of emtricitabine, 88 parts of fillers, and 28 parts of disintegrants.
4. The emtricitabine alafenamide and tenofovir alafenamide compound tablets according to claim 3, characterized in that: The lubricant is any one of magnesium stearate, stearic acid, hydrogenated vegetable oil, glyceryl behenate, and sodium stearyl fumarate.
5. The emtricitabine alafenamide and tenofovir alafenamide compound tablets according to claim 3, characterized in that: The disintegrant is any one of starch, cellulose, cross-linked PVP, sodium starch glycolate, and cross-linked sodium carboxymethyl cellulose.
6. The emtricitabine alafenamide and tenofovir alafenamide compound tablets according to claim 3, characterized in that: The filler is at least one of microcrystalline cellulose, mannitol, lactose monohydrate and sodium chloride.
7. The emtricitabine and tenofovir alafenamide compound tablets according to claim 6, characterized in that: The filler is composed of microcrystalline cellulose: sodium chloride = 1:0.5-1:3, wherein the model of the microcrystalline cellulose is: Avicel PH113.
8. The method for preparing the emtricitabine and tenofovir alafenamide compound tablets according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Grind tenofovir alafenamide hemifumarate and emtricitabine and control the particle size D 90 150-200μm, for standby use; S2, mixing the prescribed amount of tenofovir alafenamide hemifumarate, emtricitabine, a filler, a disintegrant, and a lubricant, and performing dry granulation with a dry granulator to obtain first granules; S3. The first granules, the remaining amount of emtricitabine and the lubricant are mixed by a three-dimensional mixer for 5-10 minutes, and the materials are pressed into 350 mg tablet cores, a total of 1000 tablets, and then film-coated.
9. The method for preparing the emtricitabine and tenofovir alafenamide compound tablets according to claim 8, characterized in that: The particle size D of emtricitabine after crushing in step S1 90 is 150μm.
Citation Information
Patent Citations
Pharmaceutical formulations comprising tenofovir and emtricitabine
CN107847450A
Emtricitabine and tenofovir compound tablet and preparation method thereof
CN112274488A
Method and composition for pharmaceutical product
US20070077295A1
Solid oral pharmaceutical compositions comprising tenofovir and emtricitabine
WO2018099895A1
Pharmaceutical compositions comprising tenofovir and emtricitabine
WO2021091498A1
